Budgeting carbon for urbanization in China. Issue 5 (6th November 2014) - Pan, Jiahua; Liu, Jie; Zhu, Chun
Abstract : China's urbanization in the post‐reform period since 1978 is especially notable for three features: large scale, fast speed, and long process. And it is now facing challenges in land, energy, water resources, and environment. All these challenges are linked to the emissions of carbon dioxide. As China is expected to have a cap on emissions, there must be a limit to emissions over the process of urbanization in China. In this article, a comprehensive analysis is implemented aimed at budgeting carbon for China's urbanization from 2020 to 2040. By incorporating the concept and principle of ecological civilization into China's urbanization, the constraint on carbon budget not only increases the market demand for raw materials, labor, and commodities that act as the main driving forces for economic growth, but also guarantees the state energy safety and contributes to the global ecological security. WIREs Energy Environ 2015, 4:406–409. doi: 10.1002/wene.153 This article is categorized under: Energy and Climate > Climate and Environment Energy Policy and Planning > Climate and Environment Abstract :